Gambaran Tingkat Pengetahuan Tentang Kebersihan Gigi dan Mulut Pada Kelas XII SMK Karya Adi Husada Mataram - Kurniawati, Heny; Puri, Kurnia Erma; Aziz, Abdul (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Knowledge of dental and oral hygiene is very important in maintaining oral hygiene. Dental and oral hygiene is carried out to prevent dental and oral diseases, increase endurance, and improve oral function. Maintaining oral hygiene at school age is one way to improve health at an early age. This study aims to describe the level of knowledge about oral hygiene in class XII SMK Karya Adi Husada Mataram. The type of research used is descriptive survey research, which is a research method that takes a sample from a population and uses a questionnaire as a data collection tool to see the level of knowledge of dental and oral hygiene in Class XII SMK Karya Adi Husada Mataram. From the examination conducted at SMK Karya Adi Husada Mataram, it was found that the results of OHI-S scores on 30 students who had been examined were 3 students with good OHI-S scores, 10 students with moderate OHI-S scores, and 17 students whose OHI-S scores bad. The conclusion of this study is the level of knowledge about oral hygiene, the results can be obtained from the majority of respondents with moderate knowledge of 16 respondents.